LOCAL WISDOM AS AN ENVIRONMENTAL CONSERVATION ENDEAVOR IN SELALEJO VILLAGE AND EAST SELALEJO VILLAGE, MAUPONGGO DISTRICT, NAGEKEO REGENCY - Kosmas, Ebu; Tupen, Rafael (International Journal of Research -GRANTHAALAYAH, 2023)
The indigenous community of Selalejo possesses a local wisdom known as "Tanda," which proves highly effective in the preservation of the environment. "Tanda" signifies the act of providing symbols or codes in the form of young palm leaf shoots, primarily attached to trees at specific locations along with the jawbone of a pig, after its meat has been consumed during a customary ritual signifying the commencement of indigenous law related to "Tanda”. Through the presence of "Tanda," the environment, including land, forests, plantation crops, and crops, is safeguarded from logging, harm, and the threat of looting or theft through the symbolic messages conveyed by the arrangement of leaves and pig jawbones hung on these trees. The philosophical foundation of "Tanda" is rooted in the idea that humans and the natural environment are inseparable entities. This connection is grounded in the belief that the earth and water constitute the body and blood of humanity, which manifest in the form of a mother (Mother Earth) upon which all plants and vegetation thrive. Moreover, various religions hold the view that the entire universe (earth, water, and the life upon it) is the creation of God. Human beings are entrusted with the responsibility of stewardship, which entails safeguarding, preserving, and managing these resources in a responsible and non-arbitrary manner. The existence of the "Tanda" customary law within the indigenous community of Selalejo serves as a social control mechanism and a tool for social engineering aimed at transforming undesirable behaviors related to irresponsible and arbitrary resource utilization. In cases of violations of the "Tanda" customary law, enforcement is carried out by traditional institutions.